The political Thought of José Gaos. The Criticism of Totalitarianism - Sánchez Cuervo, Antolín (Pensamiento. Revista de Investigación e Información Filosófica, 2017)
Jose Gaos’s diverse writings are reviewed, many of them scantily known and still unpublished, related to the area of the politics in the wide sense of the term. It was the case of some reflections motivated by the global protagonism of the war, the totalitarianism and the technocracy in the current manners of life, including those that are typical of the democratic western companies. In line with this protagonism, Gaos raised a genealogical review of the secularizing process of modern rationality, which will connect with some of his big worries, such as the possibility of the philosophy itself and the possibility of the Hispanic philosophy especially.